PELAKSANAAN PENGAWASAN BARANG DAN JASA BEREDAR OLEH SEKSI PERLINDUNGAN KONSUMEN PADA DINAS PERINDUSTRIAN DAN PERDAGANGAN KOTA PEKANBARU - Made Devi Wedayanti; Zulkifli Zulkifli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2015)
This study aimstoinvestigate the implementation of surveillance conducted by the Department of Industryand Supervision through of Development and Protection of electronic goods and servicesin the cityof Pekanbaru. Assessment indicator susedinclude the determination of the standard implementation, measurement Determination of activity implementation, measurement of the implementation of activities, comparison and analysis of the implementation of the standard deviation, Taking corrective action when .Metode the methodof research useda combination of qualitative and quantitative. The location of this researchin the Department of Industryand Trade of Pekanbaru witht wogroups of the population and the samplein this study are employees of guidance andprotection, amounting to 7 people, then business communities Merchan diseand/ Services Electronic numbering 14 people. Based on this analysis technique researc hersassess and concludethat the implementation of Goods and Services Supervision Circulating By Consumer Protection Sectionat the Officeof Industry and Tradeof Pekanbaruis in the interval Recommendation sassessment done enough to be considered, especially with regard to the implementation of supervision must be optimized again to protect the public from electroniccirculation of goods and servicesthat do not conformto the standard.